Postural sway response to rebound jumps of different duration - Zemkova, E.; Kyselovicová, O.; Hamar, D. (Human Movement, 2010)
The study compares the sway variables after continuous CMJs eliciting different level of proprioceptive stimulation determined by percentage of max height of the jump. Basic procedures. A group of 11 aerobic dancers performed in random order repeated jumps with maximal effort until the jump height dropped to 75%, 50%, and 25% of previously established max jump achieved in non-fatigued conditions. The height of CMJs was calculated from flight times registered by FiTRO Jumper. Thirty seconds prior to and two minutes after exercises the COP velocity was registered at 100 Hz by means of posturography system FiTRO Sway Check based on dynamometric platform. Main findings. Results showed that max height of the jump (MJ) decreased from 27.7 ± 2.8 cm to 20.1 ± 2.6 cm when subjects matched 75% of 1MJ, to 13.8 ± 1.6 cm at 50% of 1MJ, and to 6.9 ± 0.8 cm at 25% of 1MJ. The COP velocity was significantly (p </= 0.01) higher after jumps dropped to 75% of 1MJ as compared to baseline (from 9.2 ± 1.6 mm/s to 14.5 ± 2.4 mm/s). Its further significant (p </= 0.05) increase was observed after jumps dropped to 50% of 1MJ (to 19.6 ± 2.6 mm/s). However, there was only slight increase in COP velocity after jumps dropped to 25% of 1MJ (to 21.4 ± 3.2 mm/s). Conclusions. Taking into account a gradual increase in sway velocity after jumps matched 75% and 50% of 1MJ and its no further increase after jumps matched 25% of 1MJ, it may be assumed that post-exercise balance impairment is not linearly related to the level of proprioceptive stimulation.